Corrosion behavior and mechanisms of Al2O3 and Mo coated Zircaloy-4 in high-temperature lithiated water. (June 2022) - Jiang, Guanyu; Xu, Donghai; Guo, Shuwei; Liu, Lu; Hao, Botian; Wang, Mingjun
Abstract: Anti-corrosion coatings on Zircaloy cladding have been extensively explored to guarantee the safe operation and scale up industrialization of nuclear reactors. In this work, Mo and Al2 O3 powders were successfully coated on Zircaloy-4 by air plasma spraying. Their morphologies, phases of corrosion products and hardness were analyzed. After exposure to lithiated water at 360 °C and 18.5 MPa for 500 h, Mo coating fell off and complex phases were formed on the residual bonding layer. The corrosion products were NiO(OH), MoO3, Mo sub-oxides, ZrO2, Zr sub-oxides, Al2 O3, intermetallic Ni-Al compound, Li2 Ni2 (MoO4 )3, NiCr2 O4 and NiFe2 O4 . Corrosion mechanism of Al2 O3 coating was discussed in details. Cracks and pores evolved on the coating, and the surface phases were dominantly Al2 O3 and AlO(OH). ZrO2, SnO, intermetallic Zr-Al, Ni-Al-O, Li-Al-O, NiFe2 O4 and NiCr2 O4 were also detected in the presence of LiOH. Graphical Abstract: ga1 Highlights: Mo and Al2 O3 coatings were fabricated on Zircaloy-4 by air plasma spraying. Mo coating exhibited brittle fracture and seriously peeled off. Pitting corrosion and local oxidation occurred on the surface of Al2 O3 /Zircaloy-4. Hydrates, oxides, intermetallic compounds and deposits were corrosion products.